REVIEW JURNAL: ORGANISME SEL STOMATA PADA DAUN ADAM HAWA - Oktalia Putri, Dina; Mustakim, Ardi (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Stomata are microscopic structures located on the surface of leaves and function as an entrance for gases such as carbon dioxide (CO₂) and oxygen (O₂), as well as an outlet for water vapor during the transpiration process. The Adam Eve plant (Rhoeo discolor), which is known as an ornamental plant, has stomata characteristics that are interesting to study, especially in the context of adaptation to the environment and climate change. This study aims to explore various aspects of stomata in Rhoeo discolor, including distribution, size, and response of stomata to environmental factors. In this study samples, leaves were taken from several Rhoeo discolor individuals grown under similar conditions in a botanical garden. The analysis method includes measuring the area of ​​the stomata using a digital microscope and image analysis software. In addition, transpiration speed measurements were carried out using a porometer to determine the relationship between the number of stomata and transpiration efficiency. The data obtained was analyzed statistically to identify significant patterns and correlations. The results showed that Rhoeo discolor has varying stomata density depending on the position of the leaf.